2012
DOI: 10.1007/s10157-011-0580-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of minimal change nephrotic syndrome with immunoglobulin A nephropathy transitioned to focal segmental glomerulosclerosis

Abstract: A 50-year-old woman with a 1-month history of lower extremity edema and a 5 kg weight increase was admitted to our hospital with suspected nephrotic syndrome in October 1999. Urine protein level was 3.5 g per day, 10-15 erythrocytes in urine per high-power field, and serum albumin level 2.5 g/dl. Furthermore, an accumulation of pleural effusion was confirmed by chest X-ray. The results of a renal biopsy indicated slight mesangial proliferation in the glomeruli by light microscopy, and an immunofluorescence stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The single pathologic finding that correlated with the presentation of full NS was extensive (median=90%) foot process effacement. The clinical and biopsy findings in these 17 patients, as well as similar cases that have been previously reported (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), are most consistent with mild IgAN with superimposed MCD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The single pathologic finding that correlated with the presentation of full NS was extensive (median=90%) foot process effacement. The clinical and biopsy findings in these 17 patients, as well as similar cases that have been previously reported (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), are most consistent with mild IgAN with superimposed MCD.…”
Section: Discussionsupporting
confidence: 84%
“…Many of the patients are rapidly responsive to treatment with corticosteroids. Such cases are uncommon but have been presented as case reports and in small series over the last 30 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some of these reports have suggested that the clinical and pathologic findings in these unusual cases of IgAN (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), as well as the clinical outcomes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), are more typical of mild IgAN with superimposed MCD.…”
Section: Introductionmentioning
confidence: 99%
“…IgA nephropathy patients without hematuria may have nephrosclerosis or hereditary nephritis with concomitant glomerular IgA deposition, because 4 % of normal persons without urinary abnormalities are reported to have glomerular IgA deposition on postmortem examination after accidental death [7]. Concomitant glomerular IgA deposition has been reported in hereditary nephritis, including thin basement membrane disease [810], mild Alport syndrome [11], focal segmental glomerulosclerosis [12], and complement factor abnormalities [13]. Moreover, the CR rate in patients without proteinuria (mainly hematuria alone) is relatively low, 60.8 % compared to approximately 73.0 % in patients with 0.3–0.69 g/day of urinary protein.…”
Section: Discussionmentioning
confidence: 99%